Konflik Psikologis Tokoh Utama dalam Novel Budak Teuneung Karya Samsoedi - Alamsyah, Zulfikar; Kosasih, Dede (LOKABASA, 2020)
This research is based on psychological conflict experienced by children when experiencing fatherless. This case is reflected in a children's literary work with the title Budak Teuneung by Samsoedi. The purpose of this study is to describe the facts of the story, the characteristics of the main character, and the forms of psychological conflict that occur in children who experience fatherless and its causes and consequences. The method in this study is a descriptive method of reading and note-taking techniques to describe the facts of the story, the character of the main character, the psychological conflict of the main character, and their causes and consequences. The results of this study include three things, the first is the facts of the story and theme. The facts of the story include the characters, plot, and setting. The theme of this novel is orphans who have the courage to uphold the truth. The protagonist in this novel is Warji, while the main antagonist is Utun. The plot in this novel is a forward plot with 23 place settings, 7 time settings, and 5 socio-cultural backgrounds. Second, the main character of this novel is included in the character of the formal operational stage children with 11 characteristics. Third, psychological conflicts experienced by the main characters are four kinds, one of  the most dominant is approach-avoidance conflict with eight causative factors and six effects experienced. In conclusion, the facts of the story in this novel are mutually sustainable. The main character in this novel is at the formal operational stage. Then, aproach-avoidance conflict is more dominant experienced by the main character after experiencing fatherless. This indicates that the fatherless effect does not have much effect on Warji because he still has a mother figure who always educates and helps him. AbstrakPenelitian ini didasari oleh konflik psikologis yang dialami anak yang ditinggalkan ayahnya (yatim). Kasus ini tercermin dalam sebuah karya sastra anak dengan judul Budak Teuneung karya Samsoedi. Tujuan dari penelitian ini adalah untuk mendeskripsikan fakta cerita, karakteristik tokoh utama, dan bentuk konflik psikologis yang terjadi pada anak yatim beserta sebab dan akibatnya. Metode dalam penelitian ini adalah metode deskriptif dengan teknik membaca dan mencatat untuk mendeskripsikan fakta cerita, karakter tokoh utama, konflik psikologis tokoh utama, beserta sebab dan akibatnya. Hasil dari penelitian ini meliputi tiga hal, yang pertama adalah  fakta cerita dan tema. Fakta cerita tersebut meliputi tokoh, alur, dan latar. Tema novel ini adalah anak yatim yang memiliki keberanian untuk menegakkan kebenaran. Tokoh protagonis dalam novel ini yaitu Warji, sedangkan tokoh antagonis utamanya adalah Utun. Alur dalam novel ini adalah alur maju dengan 23 latar tempat, 7 latar waktu, dan 5 latar sosial budaya. Kedua, tokoh utama novel ini termasuk kedalam karakter anak tahapan oprasional formal dengan 11 karakteristik. Ketiga, konflik psikologis yang dialami tokoh utama terdpat empat macam, salah satu yang paling dominan adalah approach-avoidance conflict dengan delapan faktor penyebab dan enam akibat yang dialami. Kesimpulannya, fakta cerita dalam novel ini saling berkesinambungan. Tokoh utama dalam novel ini berada pada tahapan oprasional formal. Lalu, konflik aproach-avoidance lebih dominan dialami oleh tokoh utama setelah ditinggalkan ayahnya. Hal ini menandakan bahwa efek kehilangan sosok ayah tidak begitu banyak berpengaruh terhadap Warji karena ia masih memiliki sosok ibu yang selalu mendidik juga membantunya.